2023
DOI: 10.1021/acs.jpclett.3c01040
|View full text |Cite
|
Sign up to set email alerts
|

Stability of 20S Proteasome Configurations: Preopening the Axial Gate

Abstract: Mass spectrometry studies of the stability of the S. cerevisiae 20S proteasome from 11 to 55 °C reveal a series of related configurations and coupled transitions that appear to be associated with opening of the proteolytic core. We find no evidence for dissociation, and all transitions are reversible. A thermodynamic analysis indicates that configurations fall into three general types of structures: enthalpically stabilized, tightly closed (observed as the +54 to +58 charge states) configurations; high-entropy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
14
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 25 publications
3
14
0
Order By: Relevance
“…35 Thus, inefficient PI31−20S complex formation likely reflects the low probability of the open-gate state of the latent proteasome, and PI31 may gain entrance to the proteasome only during transient gate openings. 15,50,51 In contrast, PI31 inhibited open-gated proteasomes more efficiently across a range of PI31 concentrations. Although gate opening is obligatory for entry of PI31 into the interior of the proteasome, PI31 must also transit through the antechamber to reach the catalytic sites.…”
Section: ■ Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…35 Thus, inefficient PI31−20S complex formation likely reflects the low probability of the open-gate state of the latent proteasome, and PI31 may gain entrance to the proteasome only during transient gate openings. 15,50,51 In contrast, PI31 inhibited open-gated proteasomes more efficiently across a range of PI31 concentrations. Although gate opening is obligatory for entry of PI31 into the interior of the proteasome, PI31 must also transit through the antechamber to reach the catalytic sites.…”
Section: ■ Discussionmentioning
confidence: 94%
“…Pore occlusion appears to be the constitutive state of cellular 20S proteasomes, thereby rendering them catalytically inert. 14,15 Purified, isolated 20S proteasomes, however, can be activated in vitro by a variety of agents, including nondenaturing concentrations of SDS, 16,17 heat, 18 certain short peptides, 19−21 lipids, 17 and small molecules. 22 Such effects suggest that 20S proteasomes may be activated to catalyze protein degradation in intact cells, a role supported by numerous reports.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[31][32][33] Protein melting curves are obtained from MS data by monitoring the average charge state of each analyte or the relative abundance of conformers identified by ion mobility spectrometry. Variable-temperature electrospray ionization (vT-ESI), in which the solution temperature is varied during electrospray, has been used to determine the T m values of proteins, [34][35][36][37][38][39] protein complexes, 19,34,[40][41][42][43][44][45][46] protein as well as DNA complex unfolding pathways, 42,[47][48][49] and the thermochemistry of ligand-binding to protein-and DNA-ligand complexes. 38,47,50,51 In combination with ion mobility spectrometry, thermochemical values can be determined for individual groups of closely related protein conformers.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, native mass spectrometry (nMS) with nondenaturing electrospray ionization (nESI) has become a powerful tool for monitoring the protein dynamic structures and protein–protein interactions with the advantages of high sensitivity, high throughput, and can simultaneously detect different components in complex mixtures. To get the molecular details of protein structure changes, the native top-down MS (nTDMS) strategy can be utilized with the combination of advanced dissociation methods such as ultraviolet photodissociation (UVPD) , and electron capture/transfer dissociation (ExD). It is demonstrated that 193 nm UVPD can provide rich types of structure-informative photofragments for the characterization of protein structure alterations and protein–protein, protein–ligand interactions. On the other hand, collision induced unfolding (CIU) coupled with ion mobility-MS (IM-MS) and variable temperature-ESI MS (VT-ESI MS) are the state-of-art MS strategies for protein stability and structure unfolding analysis with high efficiency. Besides, combined with a continuous flow mixing technique, classical subsecond time-resolved ESI-MS can be realized to study the protein folding kinetics. ,, These MS strategies can characterize the overall changes in protein structures via collision cross sections (CCSs) or charge state distributions (CSDs) but without molecular details.…”
mentioning
confidence: 99%